Answer:
j = -2
Explanation:
Simplify. First, combine like terms:
(42j - 19j) + 18 = -28
23j + 18 = -28
Isolate the variable, j. Note the equal sign, what you do to one side, you do to the other. Do the opposite of PEMDAS.
PEMDAS is the order of operation, and equals:
Parenthesis
Exponents (& roots)
Multiplication
Division
Addition
Subtraction.
~
First, subtract 18 from both sides:
23j + 18 (-18) = - 28 (-18)
23j = -28 - 18
23j = -46
Isolate the variable, j. Divide 23 from both sides:
(23j)/23 = (-46)/23
j = -46/23
j = -2
j = -2 is your answer.
~